2020
DOI: 10.1111/tgis.12596
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal prediction of land surface temperature using semantic kriging

Abstract: Spatio‐temporal prediction and forecasting of land surface temperature (LST) are relevant. However, several factors limit their usage, such as missing pixels, line drops, and cloud cover in satellite images. Being measured close to the Earth's surface, LST is mainly influenced by the land use/land cover (LULC) distribution of the terrain. This article presents a spatio‐temporal interpolation method which semantically models LULC information for the analysis of LST. The proposed spatio‐temporal semantic kriging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Cokriging refers to a family of methods that incorporate associated variables into the kriging models. Cokriging has the same variants as kriging-simple, ordinary, and universal-and it tends to perform better than its univariate counterparts, as briefly dis-cussed in Section 2 (see, for example, [14]). However, in this study, none of the ancillary variables available (i.e., those presented in Table 1) was sufficiently correlated with the target variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cokriging refers to a family of methods that incorporate associated variables into the kriging models. Cokriging has the same variants as kriging-simple, ordinary, and universal-and it tends to perform better than its univariate counterparts, as briefly dis-cussed in Section 2 (see, for example, [14]). However, in this study, none of the ancillary variables available (i.e., those presented in Table 1) was sufficiently correlated with the target variable.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Wu and Li [13] argued that the temperature could be more accurately interpolated when the variable 'altitude' was included in the model, along with latitude and longitude. Bhattacharjee et al [14] also demonstrated that a cokriging model incorporating a range of weather variables into the temperature prediction could produce more precise estimations than a model relying only on distances.…”
Section: Past Studiesmentioning
confidence: 99%